Analisis Keadilan dalam Putusan Lepas Akibat Dakwaan Obscuur Libel - Bryan, Bryan; Adhari, Ade (Syntax Literate, 2023)
In the words judiciary and court both contain the word "fair" which indirectly indicates that the justitiabelen expects to obtain justice through the judicial process conducted in court. However, the law enforcement process does not always run smoothly. In fact, sometimes law enforcement is hindered due to deficiencies in the indictment which results in the indictment being materially defective so that it must be declared null and void and an acquittal is issued, as happened in the case of the Jakarta High Court Decision Number 253/PID.SUS/2021/PT.DKI. The formulation of the problem raised is the Analysis of Justice in Release Decisions Due to Unclear and Complete Charges and legal remedies for Analysis of Justice in Release Decisions Due to Unclear and Complete Accusations (Study of Decision of the Jakarta High Court Number 253/PID.SUS/2021/PT.DKI). The type of research used is normative by using secondary data collected by library research. The data is presented descriptively and analyzed using deductive logic with a statutory approach and a case approach. The results of the study show that in this decision the judge has safeguarded the rights of the accused as a form of fulfilling justice in the perspective of numerical equality but, on the other hand, the decision handed down by the judge does not reflect corrective justice. There are preventive measures to avoid acquittal decisions by collaborating between investigators and public prosecutors.